Integrated Computing and Storage for Space Transport Network Architecture - DING Chunxu; DING Xihao; DING Wenhui; XU Zhiping; YU Zhigang; LU Zhou (天地一体化信息网络)
Facing the new generation of ubiquitous communication and integrated service network characterized by "networks everywhere and computing omnipresent", diverse business applications have multi-dimensional resource requirements for computation, storage, and networking. At the same time, in the high-dynamic, weakly-connected scenarios of satellite networks, how to efficiently schedule and coordinate the multi-heterogeneous storage and computing resources of both space and ground, collaboratively optimize the networking, transmission, and storage mechanisms, establish a space-based computing, storage, and network joint resource optimization model, and provide high-quality space-based carrying network services is an important issue that urgently needs to be resolved. In response to this issue, based on the research and analysis of the development status of space-based computing and storage integration technology and its impact on the space-based carrying network architecture, a space-based carrying network architecture with computing and storage integration was proposed. From the perspectives of networking optimization, transmission optimization, storage optimization, and service optimization, the advantages of the computing and storage integrated space-based carrying network architecture compared to the traditional space-based carrying network architecture were systematically analyzed. The key technologies were summarized and refined, with the aim of providing valuable suggestions and references for subsequent research, construction, and standardization of satellite networks.